2023
DOI: 10.3390/ijms24021452
|View full text |Cite
|
Sign up to set email alerts
|

The Monocytic Cell Line THP-1 as a Validated and Robust Surrogate Model for Human Dendritic Cells

Abstract: We have implemented an improved, cost-effective, and highly reproducible protocol for a simple and rapid differentiation of the human leukemia monocytic cell line THP-1 into surrogates for immature dendritic cells (iDCs) or mature dendritic cells (mDCs). The successful differentiation of THP-1 cells into iDCs was determined by high numbers of cells expressing the DC activation markers CD54 (88%) and CD86 (61%), and the absence of the maturation marker CD83. The THP-1-derived mDCs are characterized by high numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…When compared to original THP-1 cells our recent study confirmed the expected pronounced ability of THP-1-derived iDCs to phagocytose pathogen membrane particles such as zymosan. Furthermore, iDCs, but not undifferentiated THP-1 cells, are able to induce T cell activation via upregulation of IL-12p40 upon sensitizer treatment (41). Thus, a logical subsequent step is to prove whether the iDCs might be suitable surrogates for dermal dendritic cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When compared to original THP-1 cells our recent study confirmed the expected pronounced ability of THP-1-derived iDCs to phagocytose pathogen membrane particles such as zymosan. Furthermore, iDCs, but not undifferentiated THP-1 cells, are able to induce T cell activation via upregulation of IL-12p40 upon sensitizer treatment (41). Thus, a logical subsequent step is to prove whether the iDCs might be suitable surrogates for dermal dendritic cells.…”
Section: Resultsmentioning
confidence: 99%
“…Immature dendritic cells were generated according to the protocol described by Hölken and Teusch (41). In total, 1 x 10 6 THP-1 cells were seeded in 5 mL RPMI-1640 (Gibco, #22400089) containing 10% FBS (Gibco, #10270-106), 50 U/mL Pen-Strep (Gibco, #15140122) and 50 µM 2-mercaptoethanol (Gibco, #21985023) into a T25 flask.…”
Section: Generation Of Immature Dendritic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…THP-1 cells were cultured and maintained in RPMI 1640 GlutaMAX medium (Gibco) supplemented with 10% (v/v) heat-inactivated FBS and a 1% (v/v) penicillin and streptomycin mixture (Gibco). THP-1 cells were induced to differentiate into macrophages using 100 ng/mL Phorbol 12-myristate 13-acetate (PMA) as described previously, and 100 ng/mL recombinant human interleukin 4 (IL-4) and 100 ng/mL recombinant human granulocyte macrophage colony-stimulating factor (GM-CSF) were used to induce THP-1 cells to differentiate into dendritic cells (moDC) . All cells were cultured at 37 °C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Fresh cytokinesupplemented medium was exchanged every 2 days. On day 7, the semi-adherent and cells in suspension were harvested, consisting of immature DCs (modi ed from Holken et al [14]).…”
mentioning
confidence: 99%